Metal-free oxidative cyclization of 2-aminobenzothiazoles and cyclic ketones enabled by the combination of elemental sulfur and oxygen. Issue 18 (30th August 2017) - Xie, Yanjun; Chen, Xiangui; Wang, Zhen; Huang, Huawen; Yi, Bing; Deng, Guo-Jun
Abstract : Aerobic cyclization of 2-aminobenzothiazoles and cyclic ketones enabled by the combination of elemental sulfur and oxygen under metal-free conditions. Abstract : Metal-free oxidative cyclization for the one-pot synthesis of benzo[ d ]imidazo[2, 1- b ]thiazoles from 2-aminobenzothiazoles and cyclic ketones is described. Elemental sulfur combined with molecular oxygen as the benign co-oxidant was found to be unique and highly effective to promote this transformation without the aid of any metal salts. Various cyclic ketones smoothly reacted with 2-aminobenzothiazoles to give functional benzo[ d ]imidazo[2, 1- b ]thiazoles in good to very high yields, which thereby demonstrated the synthetic convergence of this methodology.